2009
DOI: 10.1088/0022-3727/42/22/225210
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electron attachment and detachment in vibrationally excited oxygen

Abstract: Three-body electron attachment to O2 molecules and electron detachment from ions have been theoretically studied in vibrationally excited oxygen and O2-containing mixtures. Assuming that electron attachment and detachment proceed via the formation of vibrationally excited temporary ions, the rates of these processes were determined on the basis of the statistical approach for the vibrational transfer and relaxation in collisions between ions and O2 molecules. The calculated attachment and detachment rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Since dissociation is an important process in plasma kinetics, as it leads to the depopulation of the vibrational levels, in the present letter we wish to extend our previous work to dissociative electron attachment (DEA) and to resonant electron impact-dissociation (EID) of CO, taking place through the temporary formation of the resonance ( ) Π − CO X 2 . DEA is known to be a relevant process that produces stable negative ions of oxygen [9]. The reactions considered here, respectively for DEA and EID processes, are the following:…”
Section: Plasma Sources Science and Technologymentioning
confidence: 99%
“…Since dissociation is an important process in plasma kinetics, as it leads to the depopulation of the vibrational levels, in the present letter we wish to extend our previous work to dissociative electron attachment (DEA) and to resonant electron impact-dissociation (EID) of CO, taking place through the temporary formation of the resonance ( ) Π − CO X 2 . DEA is known to be a relevant process that produces stable negative ions of oxygen [9]. The reactions considered here, respectively for DEA and EID processes, are the following:…”
Section: Plasma Sources Science and Technologymentioning
confidence: 99%
“…5 and 6. As for the plasma discharge in О 2 [48], the main process of formation is the three body reaction (72), but the process of destruction is reaction (51) for the interaction of О 3 with radicals OH, rather than reaction (20). The frequency of О 3 termination in the last reaction is weakly dependent on the concentration of Н 2 О due to the weak depen dence of the concentration of OH on the Н 2 О content (Fig.…”
Section: Results Of Calculationsmentioning
confidence: 99%
“…The rate con stants of attachment processes increase by orders of magnitude with the effective vibrational temperature [20]. The calculation of the distributions of О 2 and Н 2 О molecules over vibrational levels, performed in the same manner as in [18], showed that the effective vibrational temperature did not exceed 330 K, since the electron impact excitation frequency was much lower than the V-T exchange frequency.…”
Section: Methods Of Calculations and Description Of The Modelmentioning
confidence: 97%
“…Adherence is not significant in this case-the case of high vibrational temperatures-as is it completely compensated by the reverse process [10,11].…”
mentioning
confidence: 84%